Pola Usaha Peternakan Kambing dan Kinerja Produktivitasnya di Wilayah Eks-Karesidenen Banyumas Jawa-Tengah - Akhmad Sodiq (Agricultural Faculty, 2010)
Goat farming pattern and their productivity in the area of eks-karesidenan banyumas, central javaABSTRACT. Goats play an important role in the livelihood of rural people in upland and lowland farming systems in the areas of Eks-Karesidenan Banyumas Central Java. The main focus of this study presented in this paper, consist of (i) documenting the regional goat farming pattern, and (ii) find out the level of goat productivity in their farming. Importance of this study related to the development strategic fof their goat farming. Study was conducted in the areas of Eks-Karesidenan Banyumas Central Java (consist of Banyumas, Purbalingga, Banjarnegara, and Cilacap regencies). Upland and lowland areas were selected by purposive sampling method. Qualitative and quantitative descriptive statistic was applied in this study. Most of goats are raised within traditional system, characterized by small-scale production. The production in upland and lowland areas focused on single purposes for producing kid goats from Peranakan Etawah (PE) and Jawa Randu (JR) breeds. PE goats focus on dual purposes for producing milk and meat are mostly found on upland. Flock size of PE and JR goats in upland and lowland ranges from 2 to 9 head (mean: 3.8 head) and from 1 to 6 head (mean: 2.7 head), respectively. Flock size of PE goat focus on dual purposes ranges from 8 to 75 head. PE and JR goats in upland and lowland were dominated by double litter, followed by single and triplets. The highest litter size (1.89 kids) was found in lowland, followed by single purpose of PE and JR goats in upland (1.78 kids), and dual purposes PE goats in upland areas (1.66 kids). Pre-weaning mortality was highest (9.5%) in lowland areas for single purpose of PE and JR goats. Does reproduction and productivity ranges from 1.76-5.24 kids/does/year and 12.92-87.42 kg/does/year, respectively. Doe productivity was lowest (12.92 kg/does/year) in single purpose of PE and JR at lowland due to low of their survival rate and weaning weight.